Longitudinal Photoreceptor Phenotype Observation and Therapeutic Evaluation of a Carbonic Anhydrase Inhibitor in a X-Linked Retinoschisis Mouse Model - Liu, Meng; Liu, Jingyang; Wang, Weiping; Liu, Guangming; Jin, Xiuxiu; Lei, Bo (Frontiers in Medicine, 2022)
Purpose: To study the long-term photoreceptor changes and to evaluate the effects of topical application of a carbonic anhydrase inhibitor (CAI) in a mouse model of X-linked retinoschisis (XLRS). Methods: Conventional electroretinograms (ERGs) and dark-adapted 10-Hz flicker ERGs were recorded in control and Rs1-/Y mice generated with CRISPR/Cas9. ON-pathway blocker 2-amino-4-phosphobutyric acid (APB) was injected intravitreally. Morphology was evaluated with histology and optical coherence tomography (OCT). Mice were treated with a CAI inhibitor brinzolamide eye drops (10 mg/ml) three times a day for 3 months. OCT and ERG findings at 1, 4, and 10 months were analyzed. Results: Negative ERGs and retinal cavities were evident in Rs1-/Y mice. Both a-wave and b-wave amplitudes decreased with age when compared with age-matched controls. The APB-isolated a-wave (aʹ) amplitudes of Rs1-/Y mice were reduced in all age groups. In dark-adapted 10-Hz flicker ERG, the amplitude-intensity curve of Rs1-/Y mice shifted down. The thickness of ONL and IS/OS decreased in Rs1-/Y mice. CAI reduced the splitting retinal cavities but didn’t affect the ERG. Conclusions: In addition to post receptoral impairments, photoreceptor cells underwent progressive dysfunction since early age in Rs1-/Y mice. Long-term CAI treatment improved the shrinkage of the splitting retinal cavity, while no functional improvement was observed.